Transformasi Pencatatan Keuangan Manual ke Digital: Studi Penyusunan Laporan Keuangan pada UMKM Toko Buah Maya di Kecamatan Sabangau, Palangka Raya - Fitri Nurcahyati; Lingkee Natalie Annisa Safitri; Anggita Dewi; Hilmi Satria Himawan; Verra Rizki Amelia; Sofyan Hakim (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This community service activity focuses on improving financial recording practices at Maya Fruit Shop, an MSME in Palangka Raya City, which previously relied on manual bookkeeping. The main objective of this activity is to help business owners switch to a more efficient and accurate digital financial recording system using the cashier application and Manager.io. The method used is Participatory Action Research, which is carried out based on transactions for three months through the stages of preparation, implementation, and evaluation. The results of the mentoring showed a significant improvement in business owners' understanding and ability to manage financial records, reducing administrative errors, and enabling the preparation of more accurate financial reports. These improvements increased the owner's confidence in making business decisions and strengthened the financial resilience of the business.